2022
DOI: 10.1186/s12866-022-02575-1
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota differs in composition between adults with type 1 diabetes with or without depression and healthy control participants: a case-control study

Abstract: Background Individuals with type 1 diabetes and those with depression show differences in the composition of the gut microbiome from that of healthy people. However, these differences have not yet been studied in patients with both diseases. Therefore, we compared the gut microbiome of people with type 1 diabetes with or without depression with matched healthy controls. Methods A case-control study was conducted in 20 adults with type 1 diabetes (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…Petrak et al found that the composition of the gut microbiota was associated with the development of depression in T1D, and no difference in α‐diversity was observed between T1D with depression and T1D without depression, while T1D with depression had a higher abundance of Megasphaera . 25 These findings hint at a potential link between specific bacterial groups and depression in people with diabetes. In our study, the Shannon, Chao1, and Ace indices of TD− were significantly higher than those of TD+, suggesting that TD+ had a lower α‐diversity of gut microbiota.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Petrak et al found that the composition of the gut microbiota was associated with the development of depression in T1D, and no difference in α‐diversity was observed between T1D with depression and T1D without depression, while T1D with depression had a higher abundance of Megasphaera . 25 These findings hint at a potential link between specific bacterial groups and depression in people with diabetes. In our study, the Shannon, Chao1, and Ace indices of TD− were significantly higher than those of TD+, suggesting that TD+ had a lower α‐diversity of gut microbiota.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, there are few studies that identified the microbial signature in T1D with depression. Petrak et al found that the composition of the gut microbiota was associated with the development of depression in T1D, and no difference in α‐diversity was observed between T1D with depression and T1D without depression, while T1D with depression had a higher abundance of Megasphaera 25 . These findings hint at a potential link between specific bacterial groups and depression in people with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher abundance of Christensenellaceae_R-7_group was positively correlated with the concentrations of reactire oxygen species (ROS) due to its imparing mitochondrial function, protein carboxyl, and interleukin-6 (IL-6) production [47] . Several studies reported that the abundance of Christenseniaceae was higher in patients with T1D and early renal function decline than in HC [48][49] . Christensenellaceae_R-7_group and Alistipes enriched in PDR group were thought to be positively associated with low-grade inflammation.…”
Section: Correlations Of the Gut Microbiota With Metabolicmentioning
confidence: 99%
“…The presence of ACEs in their lives can exacerbate this risk even further, as studies have shown the association of high ACE with increased burnout severity and depressive symptoms among nursing students [40]. Additionally, research suggests that the gut microbiota may play a significant role in influencing the development and severity of depression [41][42][43][44]. For this reason, we The gut microbiome, influenced by endogenous and exogenous factors and life events such as diet, age, stress, genetics, disease, and antibiotics, varies significantly among individuals [20,21].…”
Section: Introductionmentioning
confidence: 99%